Intolerance of Ambiguity in the Behavior of Using Accrual based Accounting Information - Hamonangan Siallagan (Universitas Hayam Wuruk Perbanas, 2022)
This research aimed to examine the effects of 1) beliefs on attitude towards the use of accrual information; 2) attitude, subjective norms and perceived behavioral control on the intention of using accrual information; 3) perceived behavioral control and intention on the behavior of using accrual information; and 4) intolerance of ambiguity as moderator on the effect of intention on the behavior of using accrual information. This study used primary data taken by administering questionnaires to the respondents. The data were analyzed usingÂ SEM-PLS approach and WarpPLS software. The results supported the first five hypotheses, except the sixth one. The research results indicated that there was a negative role of intolerance of ambiguity. Research implications suggest that the cognitive theory and the theory of planned behavior can be used to explain the behavior of using accrual information for decision making.